The right to non-discrimination as a ground for legal recognition of intersex persons in Nigeria - Sogunro, Ayodele (University of Pretoria, 2024)
Mini Dissertation (LLM (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.